Pilot investigation of selected milk-borne pathogens in communal cattle in the uMkhanyakude district of KwaZulu-Natal, South Africa - Michel, Anita Luise (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.